2017
DOI: 10.1097/md.0000000000009183
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of injured Broca's portion of arcuate fasciculus in the dominant hemisphere in a patient with traumatic brain injury

Abstract: Rationale:Recovery of injured AF in patients with traumatic brain injury (TBI) has not been reported. In this study, we report on a patient with TBI who recovered from an injury to Broca's portion of AF in the dominant hemisphere, diagnosed by diffusion tensor tractography (DTT).Patient concerns:A 28-year-old right-handed male patient suffered head trauma resulting from sliding while riding a motorcycle.Diagnoses:He was diagnosed with a traumatic contusional hemorrhage in the left frontal lobe, subarachnoid he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Several mechanisms have been proposed currently, including the contribution of either the perilesional region in the affected hemisphere or the homologous language regions in the unaffected hemisphere. [ 1 , 2 ] Thus, it is obvious that the bilateral hemispheres of brain are critical for the recovery of aphasia. In addition, a growing number of literature has pointed out that the white matter tracts play a crucial role in understanding the neural mechanisms of language processing, and determining the nature of language deficits and recovery patterns in aphasia.…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms have been proposed currently, including the contribution of either the perilesional region in the affected hemisphere or the homologous language regions in the unaffected hemisphere. [ 1 , 2 ] Thus, it is obvious that the bilateral hemispheres of brain are critical for the recovery of aphasia. In addition, a growing number of literature has pointed out that the white matter tracts play a crucial role in understanding the neural mechanisms of language processing, and determining the nature of language deficits and recovery patterns in aphasia.…”
Section: Introductionmentioning
confidence: 99%
“…Our patient was able to resume speech within a matter of days and was producing a halting speech with appropriate vocabulary and syntax by the time of discharge. Few cases have been published on traumatic insult isolated to Broca's area with no prior studies showing a pure motor deficit [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage of DTT is that the entire neural tract can be evaluated using the DTT parameters (fractional anisotropy [FA], mean diffusivity, and fiber number) and configurational analysis [ 31 , 32 , 33 ]. As a result, serial DTTs for the language-related neural tracts during the improvement phase appear to be appropriate for the elucidation of the mechanisms of aphasia recovery in them [ 8 , 18 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 34 , 35 , 36 ]. A significant number of DTT-based studies have reported on the recovery mechanisms of aphasia in various brain pathologies including stroke, traumatic brain injury, and brain tumor [ 8 , 18 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, serial DTTs for the language-related neural tracts during the improvement phase appear to be appropriate for the elucidation of the mechanisms of aphasia recovery in them [ 8 , 18 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 34 , 35 , 36 ]. A significant number of DTT-based studies have reported on the recovery mechanisms of aphasia in various brain pathologies including stroke, traumatic brain injury, and brain tumor [ 8 , 18 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 34 , 35 , 36 ]. The majority of the above studies have reported on stroke patients with aphasia [ 18 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%